Functional T cells in rabbits gut mucosal lymphocytes. Issue 5 (May 1976) - Singal, D P; O'Neill, M; Clancy, R; Bienenstock, J
Abstract : Functional studies of Peyer's patch and gut mucosa lymphocytes were performed in mixed lymphocyte culture reaction (MLC), an in vitro measure of the capacity of T cells to recognize and respond to cell surface alloantigens. The data demonstrate the functional effectiveness of both these mucosal lymphocyte populations in one-way MLC, both as responding as well as stimulating cells. Both the responding and stimulating capacities of these cells in MLC were almost the same as observed for lymphocytes obtained from either spleen or thymus. We conclude that functional T cells exist in both rabbit gut lamina propria and Peyer's patches with approximately the same quantitative capacity to respond in the MLC.